Effect of different postharvest treatments on the sensorial attributes of button mushrooms at 15oC - Gupta, Prerna (Mushroom Research, 2017)
An experiment was conducted to study the effect of different postharvest treatments i.e. chemicals and use of desiccants on the quality and shelf life of mushrooms.Â  Fresh mushrooms were given washing treatments with different concentrations of hydrogen peroxide (1.5%,2.5%, 3.5%), ethylenediaminetetra acetic acid (2%, 4%,6%) and citric acid (0.5%,1.5%,2.5%) as well as different in-package desiccants viz, sorbitol (5g, 10g), silica gel (3g, 5g), citric acid (3g, 5g) and CaCl2 (1g, 3g) which were inserted inside the package to check the changes in off odor and off color in mushrooms at 15oC. Of the different chemicals used 1.5% H2O2 was found to be most effective in preventing off-odor and off- color development in mushrooms whereas in case of desiccants sorbitol (5g) was found to be most effective in controlling the off-odor and off-color development when observed for 6 days at 15oC.